Rapiers by Juan Martinez the Elder – the royal sword-smith from Toledo found in Poland - Lech Marek (Fasciculi Archaeologiae Historicae)
The paper deals with the problem of luxury rapiers of the 16th century and their use among representatives of different stratas in the early modern society. One can observe on the example of the two analyzed specimens, manufactured in the workshop of the royal Toledan bladesmith Juan Martinez the Elder, how the increase in wealth and prosperity among burgesses has lead them to copy fashion for luxury weapons and attire from the highest nobility